Application of Liquid Smoke on Milkfish (Chanos chanos) and Catfish (Clarias batrachus) as an Effort to Improve the Smoked Products Quality - Fronthea Swastawati; Slamet Suharto; Muflihatul Muniroh; Bambang Cahyono; Defita Faridlotus Shalihah; Aninditya Artina Setiaputri (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2022)
Fish smoking in Indonesia is still used traditionally, and generally used hot smoking method. The products produced by traditional fish smoking do not meet the quality of products in accordance with Indonesian national standards (SNI). Liquid smoke can be applied to improve the quality of smoked fish products. The aimed of this activity was to the downstream the application of liquid smoke, which was invented through a research, to improve the quality and productivity of milkfish and catfish in UKM Dapoer Sehat dan Dapoer Helena, Semarang. The materials used in this research were milkfish and catfish. Both fish were processed into smoked fish using 5% liquid smoke, and these products were then analysed to discover their water activity, proximate composition, and total bacteria (TPC). The moisture contents of milkfish and catfish were 57.20 % and 59.53% respectively. The total number of bacteria (TPC) in both smoked fish had met the Indonesian smoked fish standard (SNI), which was a maximum 1 x 105 colonies/g. The smoked milkfish and catfish that were processed using liquid smoke with a concentration 5% had met the Indonesian smoked fish standard (SNI 2725:2013). The application of liquid smoke to smoked fish products can improve product quality, and the products are is safe for consumption.